Common adverse cutaneous drug reaction patterns and the causative drugs in Malaysia - N. H. Talib; M. Leelavathi; Z. Hamzah (South African Family Practice)
Background: Patients with adverse cutaneous drug reactions (ACDRs) are frequently referred from primary care to tertiary centres for further management. This causes a loss of information regarding ACDRs as these patients discontinue primary care follow-up upon referral to tertiary care. The aim of this study is to determine the prevalence and characteristics of ACDR, and to use this valuable information to enhance awareness of primary care physicians regarding this condition.